Advancing care priorities for health and quality of life among older adults in the autism and/or intellectual disabilities communities: proceedings of an international Think Tank - David B. Nicholas; Fakhri Shafai; Stephen M. Edelson; Vanessa Bal; Hilary Nelson; Wenn Lawson; Mary Doherty; Hilde M. Geurts; William F. Sullivan; B. Blair Braden; Gregory L. Wallace; Maxine Share; et al. (BMC Proceedings)
Abstract As the number of older autistic adults and adults with intellectual disabilities grows, expanding capacity to meet their needs is crucial. On November 23-25, 2023, a Think Tank on aging in autism and/or intellectual disabilities was convened, with national and international delegates within this field. The Think Tank consisted of presentations focusing on key issues as well as a series of panel presentations addressing first-person lived experience, family caregiving, service provision in the community, and physical and mental health-based care. Discussion reflected lived experiences and care needs in this population, with an ultimate aim of advancing healthcare and community support. Delegates, who represent perspectives as self-advocates, family caregivers, service providers, clinicians and researchers, ranked guidelines and areas of focus identified in the literature in terms of the most important priorities for the near-term development of capacity building resources.